POLA KOMUNIKASI PIMPINAN DALAM MEMBANGUN MOTIVASI KERJA PEGAWAI KANTOR KECAMATAN SEBATIK TENGAH (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The purpose of this study, namely: (1) To determine the pattern of leadership communication in building work motivation of the Central Sebatik District Office employees. (2) to find out how work motivation is applied by the leadership to employees at the Central Sebatik District Office. The results of this study indicate that the leadership communication pattern in building employee work motivation is to use all channels, namely, total channel communication patterns, chains, circles, and wheels. (1) The total channel pattern in which the leader is free to communicate with his employees, (2) The wheel pattern in which the leader is the center in determining a decision, (3) The circle pattern in which employees can also interact with other employees, and (4) ) A chain pattern in which employees can also convey one message to another message. The work motivation applied by the leadership to employees at the Central Sebatik District Office has been running very well and effectively, resulting in work motivation for employees including: (1) Work Spirit, (2) Work Discipline, (3) The ability to interact (4) Encouragement to excel (5) Employee participation in determining the goals of the leader.